Perancangan Pengendalian Risiko di Departemen Research and Development (R&D) PT Intidaya Dinamika Sejati - Vigie Frederika; I Nyoman Sutapa (Jurnal Titra, 2023)
This study focuses on managing risks in the Research & Development Department. Through the utilization of interview and brainstorming techniques, a total of 37 identified risks stemming from 14 specific work activities.The Risk Management Form was employed as a tool to facilitate the risk identification process. Out of the 37 risks, four risks were given priority for the implementation of risk control measures. The prioritization was based on the severity level of the risks and the time constraints associated with conducting further research. The risks selected for risk control design were as follows: the risk of sketches and specification calculations not aligning with customer demands, the risk of inaccessible reference image files, the risk of revising drawings, and the risk of drawing delays. The proposed risk control designs aimed to mitigate the severity of these risks and consisted of the creation of a drawing aimed to mitigate the severity of these risks and consisted of the creation of a drawing request form, standardization of folder and file naming conventions for drawing references, and the establishment of standard operating procedures (SOP).